Dampak Peningkatan Konsentrasi Deterjen terhadap Kualitas Air dan Respons Perilaku Ikan Nila (Oreochromis niloticus) - Helmy Akbar; Bagus A. Utomo; Muhammad Isnan Zuhri; Wiwid Arif Pambudi; Esraa E. Ammar; Hefni Effendi (Jurnal Ilmiah Samudra Akuatika, 2025)
The increased use of detergents during the COVID-19 pandemic has raised concerns regarding their impact on aquatic environments, particularly water quality and aquatic biota. Even prior to the pandemic, the effects of detergent exposure on water quality and aquatic organisms had been studied, but the surge in hand soap and cleaning product usage has likely led to higher concentrations of Linear Alkylbenzene Sulphonate (LAS), a common active ingredient. This study aimed to determine the median lethal concentration (LC50) of detergent compounds, observe behavioral changes in Oreochromis niloticus (Nile tilapia), and examine histopathological damage to gill tissues following exposure. The LC50 value was determined to be 0.061 mg/L, with an effective concentration range between 0.059 mg/L and 0.063 mg/L. Behavioral responses observed in exposed fish included disorientation, reduced responsiveness, and lethargic movements. Histological analysis revealed significant damage to the gill tissue in exposed specimens compared to the control group. These findings indicate that increased detergent concentrations in aquatic environments may pose a significant threat to fish health and overall ecosystem stability.